18 anos do Programa Bolsa Família: Trajetória e análise dos resultados - Feitosa, Geovana Monteiro de Noronha (2023)
The present study aims to analyze the trajectory and the social and economic effects of the Bolsa Família Program from 2003 to 2021 which was designed to provide and guarantee basic income for families living in poverty and extreme poverty through conditional cash transfers. Initially, the study contextualizes the problem of poverty and presents the historical background of social policy in Brazil. The program's characteristics, target audience, benefits, and conditionalities are also presented. The study analyzes the program's results, including its effects on poverty reduction, promotion of education and health, and explores the multiplier effect on the economy. The myth surrounding the "laziness effect" is also discussed. Finally, the current status of the program is addressed, comparing it to the new Auxilio Brasil program. Over its eighteen years, the Bolsa Família Program has played an important role in improving health conditions and combating social inequality. This research is bibliographic in nature and is based on the works of the following main authors: Marcelo Neri (2013), Tereza Campello (2013), Pedro H. G. Ferreira de Souza (2018), Sergei Soares (2010).